Restoration of degraded soils with perennial pastures shifts soil microbial communities and enhances soil structure - Aban, Carla Luciana; Larama, Giovanni; Ducci, María Antonella; Huidobro, Dina Jorgelina; Sabaté, Daniela; Vargas Gil, Silvina; Perez Brandan, Carolina (Elsevier, 2025)
The expansion of agricultural lands has been associated with significant degradation of soil ecosystems. Traditional agricultural practices such as monoculture, minimal crop rotations, excessive pesticide use, and intensive tillage have resulted in soil degradation, negatively impacting nutrient cycling, carbon sequestration, biodiversity, and water retention. This study aimed to investigate the transition from a 50-year-old degraded soil to an intermediate stage of restoration achieved through a 12-year revegetation using the perennial pasture Brachiaria brizantha. Soil chemical, physical, and microbiological properties and the changes in microbial abundance on the bacterial 16S rRNA gene were assessed. Our results indicate that Brachiaria brizantha, through its associated bacterial microbiome, significantly improved soil chemical, physical, and microbiological properties, enhancing soil organic carbon, total nitrogen, and aggregate stability, with aggregate stability emerging as the principal factor being influenced by the bacterial community. The introduction of Brachiaria pastures exhibited enrichment of Nitrosomonadaceae, Sphingomonas, and Gemmatimonas, facilitating nitrogen cycling processes and increased carbon and nitrogen microbial biomass. This transition suggests a partial restoration of soil microbial biodiversity and functions, highlighting the potential of Brachiaria brizantha as an effective tool for soil restoration and sustainable agricultural practices.